2011
DOI: 10.1007/s11302-011-9278-z
|View full text |Cite
|
Sign up to set email alerts
|

Using antibodies against P2Y and P2X receptors in purinergic signaling research

Abstract: The broad expression pattern of the G protein-coupled P2Y receptors has demonstrated that these receptors are fundamental determinants in many physiological responses, including neuromodulation, vasodilation, inflammation, and cell migration. P2Y receptors couple either Gq or Gi upon activation, thereby activating different signaling pathways. Ionotropic ATP (P2X) receptors bind extracellular nucleotides, a signal which is transduced within the P2X protein complex into a cation channel opening, which usually l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…P2X 7 receptor is expressed in SCG [20,41]. In some tissue P2X 7 antibody gives positive reaction in P2X 7 KO mice probably interacting with splice variants of the P2X 7 receptors [8]. Our results showed that MI rats displayed higher levels of P2X 7 immunoreactivity, mRNA, and protein in SCG.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…P2X 7 receptor is expressed in SCG [20,41]. In some tissue P2X 7 antibody gives positive reaction in P2X 7 KO mice probably interacting with splice variants of the P2X 7 receptors [8]. Our results showed that MI rats displayed higher levels of P2X 7 immunoreactivity, mRNA, and protein in SCG.…”
Section: Discussionmentioning
confidence: 52%
“…After washed by PBS for three times, the sections were incubated in 3 % H 2 O 2 for 10 min to block the endogenous peroxidase. Following rinses in PBS, sections were incubated with 5 % BSA for 60 min, then the sections were incubated with rabbit anti-P2X 7 (1:100; Alomone Labs, Jerusalem, Israel) [8], rabbit anti-P2X 3 (1:2,500, Millipore International, Inc, USA), mouse anti-GS (1:100 dilution; Abcam Inc., USA), mouse anti-NeuN (1:200 dilution, Millipore International, Inc, USA), rabbit monoclonal anti-CGRP (1:500 dilution, bioss, CO), rabbit monoclonal anti-SP (1:500 dilution, bioss, CO) or mouse anti-TH (1:1,000 dilution; Abcam International, Inc. USA) diluted in PBS for overnight at 4°C. Sections were rinsed and incubated with biotinylated goat anti-rabbit secondary antibody or goat anti-mouse secondary antibody (1:100 dilution; Beijing Zhongshan Biotech.…”
Section: Immunohistochemistry and Double-label Immunofluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…Of the three antibodies we tested, our examination of the literature, indicated that APR-011 from Alomone Labs has been widely used and has been published several times with beautiful images provided in rat retina (Wurm et al, 2009, Brass et al, 2012, Zhang et al, 2012) and duodenum (Mizumori et al, 2009, Brass et al, 2012) and Western blot data provided in cell lines (Lau et al, 2011, Tamaishi et al, 2011). One reason this antibody is so compelling is its ability to discriminate between cell types and produce specific staining patterns within a tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the sections were incubated with horseradish peroxidase (HRP)-marked goat anti-rabbit or donkey antigoat IgG in PBS for 1 h and then reacted with color at room temperature, timely terminating the color reaction, hematoxylin counterstain, dehydration, and transparention and observing under the microscope (Olympus, Japan) and taking photograph. The primary antibodies were rabbit anti-P2X1-5, 7 antibodies, at 1:200 proportional dilution (Alomone Labs, Israel) [15], and goat anti-P2X6 antibody, at 1:100 dilution (Santa Cruz, USA). The second antibodies were HRP-conjugated goat anti-rabbit and donkey anti-goat IgG (1:1000, Santa Cruz Inc., USA).…”
Section: Ihc Stainingmentioning
confidence: 99%